녹차씨에서 분리한 물질의 Candida albicans에 대한 저해 활성 - 서예슬(Ye-Seul Seo); 양은주(Eun Ju Yang) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2018)
녹차씨에 함유된 항효모 물질의 분리를 위하여 녹차씨의 물 추출물을 여러 용매를 사용하여 순차 분획하고 각 분획층의 항효모 활성을 측정한 결과 n-butanol 층이 가장 높은 활성을 나타내었다. n-Butanol 분획층을 MPLC와 HPLC를 수행하여 F4-3 항효모 물질을 분리하였으며, LC-MS/MS 분석 결과 분자량 1,230의 theasaponin E와 유사한 물질로 확인되었다. F4-3 항효모 물질에 의한 효모 세포의 손상도를 neutral red 염색법으로 조사한 결과 항효모 물질의 농도가 증가할수록 Candida albicans 세포의 vacuole 손상으로 세포질이 붉게 염색되었으며, 세포 용해에 의한 cell debris도 관찰되었다. 항효모 물질에 의한 효모 세포 투과성 변화를 crystal violet 흡수율로 관찰한 결과 항효모 물질의 농도가 증가할수록 세포 손상에 따른 crystal violet의 흡수율이 증가하였다. 항효모 물질을 처리한 C. albicans 세포의 형태를 주사전자현미경으로 관찰한 결과 세포벽 또는 세포막의 손상으로 세포 표면이 불규칙한 형태를 나타내었다. 본 연구의 결과 녹차씨 유래의 항효모 활성 사포닌은 천연보존제 및 항진균제 개발을 위한 물질로 활용될 수 있을 것이다. Our previous study showed that green tea seed extract has strong anti-yeast activity. In this study, we isolated an anti-yeast compound from water extract of green tea seeds and investigated its inhibitory effect on Candida albicans cells. Green tea seeds were extracted with water, and water extract was partitioned with chloroform, ethyl acetate, n-butanol, and H2O. The n-butanol fraction showing the highest anti-yeast activity on C. albicans was further fractionated by medium pressure liquid chromatography, after which anti-yeast compound (F4-3) was obtained using high pressure liquid chromatography. Anti-yeast compound in liquid chromatography-tandem mass spectrometry analysis presumed theasaponin E as having a molecular mass of 1,230 kDa. Anti-yeast saponin damaged cell vacuoles of C. albicans, which was analyzed by neutral red staining. Membrane permeability was assessed by crystal violet assay, and C. albicans cells treated with anti-yeast compound exhibited significant uptake of crystal violet in a concentration-dependent manner. The morphological changes of C. albicans cells were observed with a scanning electron microscope. As a result, anti-yeast saponin from green tea seeds is expected to be used as a natural preservative and anti-fungal agent. KCI Citation Count: 0